The Real Effects of Financial Sector Interventions During Crises - Valencia, Fabian (IMF Working Papers; Working Paper ;, 2011)
We collect new data to assess the importance of supply-side credit market frictions by studying the impact of financial sector recapitalization packages on the growth performance of firms in a large cross-section of 50 countries during the recent crisis. We develop an identification strategy that uses the financial crisis as a shock to credit supply and exploits exogenous variation in the degree to which firms depend on external financing for investment needs, and focus on policy interventions aimed at alleviating the bank capital crunch. We find that the growth of firms dependent on external financing is disproportionately positively affected by bank recapitalization policies, and that this effect is quantitatively important and robust to controlling for other financial sector support policies. We also find that fiscal policy disproportionately boosted growth of firms more dependent on external financing. These results provide new evidence of a quantitatively important role of credit market frictions in influencing real economic activity.